PROTOTYPE PENGUNCI PINTU OTOMATIS MENGGUNAKAN RFID (RADIO FREQUENCY IDENTIFICATION) BERBASIS MIKROKONTROLER ARDUINO UNO - Simarangkir, Manase Sahat H; Agung Suryanto (Technologic, 2020)
A manual door security system that has many shortcomings including difficulty opening locks when used, easily broken and keys that tend to be duplicated thereby reducing convenience and security. To prevent this, a good and easy-to-use room security system is needed. At this time began to develop an electronic room safety system using RFID technology (Radio-Frequency Identification) to improve the security system at the door of the house. In this study discusses the design and prototype of an automatic room door lock using an RFID system. The research method used is research and development. This Automatic Door is programmed by the Arduino application by creating a security system using Radio Frequency Identification (RFID) as a radio wave of data carrier frequencies that will be received by the receiver. The results of this study are the creation of an automatic home door security system using RFID which has a better level of security compared to manual security, so that it can cope with acts of theft in homes that are often abandoned by residents. In addition, the use of RFID can also minimize the overall lock on the house, so that every family member needs only one tag card / key to open all the locks on the door in the house.